Positivist Ideas in Lithuania in the 19th Century - Genzelis, Bronislovas (Problemos, 1973)
The positivist philosophy of the 19th century influenced different fields of human knowledge. Some Lithuanian publicists of that time are found to be well acquainted with that philosophy. Though there were no consistent followers of positivism in Lithuania at that time, some positivist ideas, however, were given wide publicity. The works by A. Comte, H. Spencer, E. Renan. Ch. Letourneau were known in Lithuania. Their ideas favoured the spreading of evolutionism and were directed against clericalism. The ethics based on positivist principles was opposed to the religious conception of Man. The positivist philosophy influenced some works by J. Adomaitis, V. Dembskis, J. Šliūpas and other publicists of the 19th century who acquainted the Lithuanian reader with positivist ideas.